Excessive maternal iced-tea intake-reversible cause of premature ductus arteriosus constriction - Lopes, Vilma; Pinho, Joana; Vieira, Beatriz; Rangel, Maria A.; Carriço, Ana; Vinhas, António (International Journal of Contemporary Pediatrics, 2024)
Premature ductus arteriosus constriction is a rare entity associated with high neonatal morbidity and mortality. Most cases are idiopathic, with the major known cause being maternal use of nonsteroidal anti-inflammatory drugs. Polyphenol-rich foods have been proven to have a deleterious fetal hemodynamic effect that can lead to premature ductal constriction. We report a case of a neonate diagnosed with premature ductal arteriosus closure, whose only risk factor was an excessive maternal intake of commercial iced-tea during pregnancy. The authors aim to raise awareness to the impact of polyphenol-rich food consumption on ductus arteriosus, since maternal dietary advice can have a major preventive role. Furthermore, a timely diagnosis and intervention can prevent significant morbidity and mortality.